Enhancing Financial Accountability: The Role of Audit Education in Managing Student Assistance Funds in Educational Institutions - Alfathan Rizqullah (Institute of Accounting Research and Novation (IARN), 2023)
This research investigates the role of audit education in assessing the effectiveness of management of poor student assistance funds within educational institutions. Through a mixed-methods approach encompassing qualitative interviews and quantitative surveys, the study explores the impact of audit education initiatives on financial accountability, transparency, and excellence in fund administration. Qualitative analysis of stakeholder perspectives reveals insights into the perceptions, experiences, and challenges associated with student assistance fund management and audit practices. Quantitative findings provide empirical evidence on the prevalence and impact of audit education programs on staff competency, fund administration practices, and compliance with regulatory requirements. The integration of qualitative and quantitative data yields nuanced insights into the strengths and weaknesses of current practices, as well as implications for policy, practice, and future research in educational finance and audit education. The study underscores the critical importance of audit education in fostering a culture of accountability, integrity, and continuous improvement within educational institutions, thereby advancing the collective goal of equitable access to education and student success.